THE HISTORY OF THE OLDEST MOSQUES - Syaimak Ismail; Muhammad Saiful Islam; Aemy Aziz (Journal of Islamic, Social, Economics and Development, 2023)
The rapid pace of trading activities at the Straits of Melaka port had attracted many traders, including Chinese merchants. Their presence in Melaka created a space for cultural assimilation between two distinct nations, resulting in a distinct development process for mosque design and style. The aim of the study is to study the form of Chinese architecture found in the three oldest mosques in the state of Melaka. Chinese architectural influence on mosque architecture in Melaka began with the arrival of Chinese craftsmen for building construction. Since the founding of Melaka, there has been a close relationship between Parameswara and China's Ming Dynasty. Melaka's early mosques were shaped like tiered pyramids and pagoda-like towers, indicating Chinese influence. The design of the oldest mosque in Melaka, which resembles a temple, looks different from standard mosques. Accordingly, this study needs to be done to determine the cause of the difference. Among them is the Kampung Keling Mosque, a 200-year-old mosque built with the generosity of a wealthy Chinese named Shamsudin, who had converted to Islam. The mosque featured not only Chinese carvings but also internal and external Chinese elements such as towers and archways. These elements clearly indicate a harmonious assimilation of Chinese and Islamic cultures. The study's findings show that the construction of these mosques was influenced by Chinese elements, which can still be seen today.